Nonpoint Pollution Caused by the Agriculture and Livestock Activities on Surface Water in the Highlands of Jalisco, Mexico - López, Hugo Ernesto Flores; Orozco, Celia De La Mora; Durán, Álvaro Agustín Chávez; Corral, José Ariel Ruiz; Vega, Humberto Ramírez; FuentesHernández, Víctor Octavio (IntechOpen, 2012)
None